AI for game developers - Bourg, David M. (Safari electronic books., 2004)
Written for the novice AI programmer, this text introduces the reader to techniques such as finite state machines, fuzzy logic, neural networks and many others in an easy-to-understand language, supported with code samples throughout the text.